Generation and characterisation of warm dense matter with intense lasers. (7th November 2017) - Riley, D
Abstract: In this paper I discuss the subject of warm dense matter (WDM), which, apart from being of academic interest and relevant to inertial fusion capsules, is a subject of importance to those who wish to understand the formation and structure of planetary interiors and other astrophysical bodies. I broadly outline some key properties of WDM and go on to discuss various methods of generating samples in the laboratory using large laser facilities and outline some common techniques of diagnosis. It is not intended as a comprehensive review but rather a brief outline for scientists new to the field and those with an interest but not working in the field directly.